MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN ARIAS - Eka Khairani Hasibuan (State Islamic University of North Sumatra, 2017)
The aims of this research are intended to examine the effect of ARIAS learning model toward the increase of student's mathematical understanding ability. The research utilized nonequivalent pre-test and post control group design. The population of this research are students of grade seven from one junior high school in Bandung. As concern, the sample comprised of 37 students in ARIAS class (experiment group) and 35 students in conventional class (control group). The research problem are to improve mathematical understanding ability. The quantitative analysis is used independent sample t-test, Mann-Whitney test, while qualitative analysis is used descriptive one. The result shows better increasing mathematical understanding ability by using ARIAS learning model than by using conventional teaching.